Coronavirus Disease 2019 Safety Measures for Sustainable Tourism: The Mediating Effect of Tourist Trust - Sarfraz, Muddassar; Raza, Mohsin; Khalid, Rimsha; Ivascu, Larisa; Albasher, Gadah; Ozturk, Ilknur (Frontiers in Psychology, 2022)
The COVID-19 pandemic is continuing to have severe effects on tourism-related industries, as safety precautions have become essential to follow. Based on this, the current study aims to explore the role of tourist’s perceptions of safety in tourism destination choice with the mediating effect of tourist trust in the context of the Chinese tourism sector. Additionally, this study considers improvements to safety measures for sustainable tourism and the benefits of the technology transformation in the travel industry due to COVID-19. For this study, a quantitative approach was used, and data were collected through convenient sampling. The questionnaire was measured on a 5-point Likert scale, and a cross-sectional approach was adopted for data analysis. The findings of this study show that the effect of the perceived safety of the social environment, perceived safety of facility and equipment elements, perceived safety of human elements, perceived safety of management elements, and perceived safety of natural environments is significant and positive on tourist destination choice. Additionally, tourist trust is a significant mediator between these elements and tourist destination choice. Further, this study concluded that COVID-19 had increased travel anxiety, with particularly negative effects on the Chinese tourism sector, but that the adoption of perceived safety measures could be beneficial in regaining tourist trust for traveling, eventually giving tourists confidence in choosing their traveling destination.